Development of a lectin binding assay for mucin-type O-glycosylated serum proteins: Identification of potential biomarkers for screening of breast cancer / Lee Cheng Siang - Lee, Cheng Siang (2017)
Mucin-type O-glycosylated proteins are known to be related to many pathological diseases, especially malignancy. Mucins such as CA 27.29, CA 125 and CA 19-9 have been actively used as biomarkers for cancer detection and monitoring. Complex biological samples like serum contain a myriad of proteins with vast concentration differences. The broad dynamic range of the proteins is likely to cause masking of the mucin-type O-glycosylated proteins which are of low abundances, and hence, their failure of being identified by any typical detection method. Further, a reliable detection assay is currently unavailable to measure total mucin-type O-glycosylated proteins of biological samples, which may contain one or more of these macromolecules of unknown structures. Therefore, the present study was generally aimed at the development of a microassay to estimate mucin-type O-glycosylated proteins that is based on binding with plant lectins. In the present study, a microassay was developed based on binding of plant lectins to the typical GalNAc-Ser/Thr structural feature of mucin-type O-glycans. Since the sugar-amino acid linkage in the mucin-type O glycosylated protein is invariably cryptic, the heterogeneous peripheral and core saccharides of model glycoconjugates were chemically removed before optimising conditions for using an enzyme-linked lectin assay (ELLA). Desialylation of the model glycoconjugates led to maximal binding of the lectins but additional treatments such as Smith degradation did not result in increased binding. Of the lectins tested for their ability to probe the desialylated O-glycans, jacalin showed the highest sensitivity followed by champedak galactose binding (CGB) lectin and Vicia villosa agglutinin (VVA). Further improvement in the sensitivity of ELLA was achieved by using microtiter plates that were pre-coated with the CGB lectin, which increased the specificity of the assay to mucin-type O-glycosylated proteins. Finally, the applicability iv of the developed sandwich ELLA to crude samples was demonstrated by estimating trace quantities of the mucin-type O-glycosylated proteins in the human serum. In the second part of the study, perchloric acid was used to enhance detection of mucin-type O-glycosylated proteins in human serum. Sensitivity and specificity of the earlier developed sandwich enzyme-linked lectin assay were significantly improved with the use of serum perchloric acid isolates. When a pilot case-control study was performed using the serum perchloric acid isolates of normal participants (n = 105) and patients with stage 0 (n = 31) and stage I (n = 48) breast cancer, higher levels of total mucin-type O-glycosylated proteins in sera of both groups of early stage breast cancer patients compared to the normal control women were demonstrated. Analysis of CGB lectin bound serum perchloric acid isolates proteins found proteoglycan 4 to vary inversely with plasma protease C1 inhibitor in both the early stages of breast cancer patients compared to the controls. The data suggest that the ratio of serum proteoglycan 4 to protease C1 inhibitor may be used for screening of early breast cancer although this requires further validation in clinically representative populations